Becoming a better boss why good management is so difficult - Birkinshaw, Julian (Gildan Audio, 2020)
Julian Birkinshaws previous book, Reinventing Management, focused on how executives can challenge deep-seated assumptions about how large organisations work, and how they can devise new and better ways of working.' This book tackles the same problems from the other direction, that is, by focusing on the choices each employee makes, every day, about how we get our work done. The goal, essentially, is to reinvent the practice of management one person at a time.' If each one of us becomes more effective in our managerial work, we dont just improve the working lives of those around us, we also become agents of change for this broader endeavour as well to build better businesses. The book is in two main parts.' The first part provides the motivation and background for the core ideas in the book: showing how important it is to take management seriously (chapter 1),' sketching out the key dimensions of management and where it usually goes wrong (chapter 2), and taking a deep dive into the worldview of the employee (chapter 3). The second part provides a detailed discussion of the three alternative perspectives: a re-interpretation of management through the eyes of the employee (chapter 4), an exploration of our own biases and frailties and how we can overcome them (chapter 5), and a discussion of the use of active experimentation to overcome the limitations and pathologies of the organisations we work for (chapter 6). The final chapter explores briefly some of the ways the profession of management might change in the future. What are the megatrends that could lead to more fundamental changes in how we get work done''' Web 2.0, demographic change (Gen Y/Gen Z), and virtual working of course; and then there is the shift in power from the West to the Asia.'' The author doesnt believe the basic activities of management are going to change dramatically, but there are inevitably going to be shifts in emphasis, and the chapter explores these. . Case examples: a large number of case studies of different' management experiments (e.g. Roche, Atlassian, Pfizer, Microsoft, Google, If).